Student Communication in Solving Tug of Taw Questions - Charizah, Minnatin; Kamiliyah, Zahirotul (Noumerico: Journal of Technology in Mathematics Education, 2023)
Communication is a way to share ideas and information so mathematical communication becomes important to consider in the process of teaching and learning mathematics. This research is qualitative research that aims to describe mathematical communication in an interview based on the standards that have been put forward by the National Council of Teachers of Mathematics (NCTM). The subjects of this study were 6th-grade elementary school students and the instruments used is a test about systems of a linear equation and also interview guidelines. The results from this study are the description of mathematical communication of the first participants is satisfied in all four of the standard communication in NCTM, which since the beginning has demonstrated high motivation in communicating mathematics. While the second participant only satisfied some standards, at the end of the interview, the second participant showed increased communication of mathematics. The second participant found a better strategy after listening to his peer’s explanation.